A similaridade no uso do microhabitat por girinos (Amphibia, Anura) reflete processos ecológicos ou filogenéticos? - Melo, Lilian Sayuri Ouchi de [UNESP] (2014)
Inumerous processes have been suggested to explain the community structure, such as competition, predation, dispersal, continental drift, environmental filtering, speciation. To comprehend the influence of these processes on a local scale provide a better understanding of the composition and species richness determinants in communities, especially physically well defined communities, as is the case of the communities of tadpoles. Our goal in this study was to investigate the influence of environmental characteristics in communities structures of tadpoles in lotic and lentic water bodies. We conducted sampling in an area of Atlantic Rain Forest in southeastern Brazil. This work is divided into two section. In the first chapter we verified which environmental microhabitat characteristics of lotic and lentic water bodies positively influence species richness. Besides species richness, we evaluated species composition in microhabitats, testing if it is determined by the environmental characteristics of microhabitats or a consequence of water bodies spatial structure. In the second chapter, we seek to investigate the relationship between continuous and discontinuous environmental gradients - considering the environmental characteristics of lotic and lentic water bodies - with the taxonomic, phylogenetic and functional diversity of tadpoles on a local scale. The results of the first chapter show that species richness in microhabitats in lentic and lotic water bodies was influenced, respectively, by the amount of vegetation and sand. The aquatic vegetation had a positively relationship with tadpoles richness, probably due to the greater amount of food and refuge from predators provided. In lotic environments, the positive relationship of species richness with sand probably due to the selection of microhabitats with lower currents, where the sand is accumulated. In contrast, species composition in lentic and lotic microhabitats was mainly ...